The Legislative Response to PTSD in the United States (1989–2009): A Content Analysis. Issue 5 (16th October 2014) - Purtle, Jonathan
Abstract: Although knowledge about posttraumatic stress disorder (PTSD) has grown over the past 40 years, PTSD policy research is undeveloped. This gap in knowledge warrants attention because policy is among the most powerful tools to prevent and mitigate the effects of PTSD. This study provides a content analysis of all bills introduced in U.S. Congress that explicitly mentioned PTSD. All bills and bill sections mentioning PTSD were coded to create a legislative dataset. Bills that addressed traumatic stress, but did not mention PTSD, were also identified as a comparison group. One hundred sixty‐one PTSD explicit bills containing 382 sections of legislative text were identified, as were 43 traumatic stress, non‐PTSD bills containing 55 sections (the 2 categories were mutually exclusive). Compared to traumatic stress, non‐PTSD sections, PTSD explicit sections were far more likely to target military populations (23.6% vs. 91.4%) and combat exposures (14.5% vs. 91.4%). PTSD, as a discrete diagnostic entity, has been largely defined as a problem unique to combat exposure and military populations in federal legislation. Research is needed to understand knowledge and perceptions of PTSD among policy makers and the public to inform science‐based advocacy strategies that translate the full spectrum of PTSD research into policy.